Implementation of The Non-Discrimination Principle Towards Layoffs (Termination of Employment) UNILAY (Case Study on PT. Yihong Novatex Indonesia Layoffs 1,126 Workers) - Arjuna, Muhammad Gaung Syah; Joesoef, Iwan Erar (Universitas Islam Sultan Agung, 2025)
This study discusses the case of unilateral termination of employment by PT Yihong Novatex Indonesia against more than 1,100 workers, which has sparked a debate over legality and fairness in industrial relations. PT Yihong Novatex Indonesia, a Chinese foreign-invested company in the textile and footwear industry, carried out mass layoffs on the grounds of operational efficiency due to a decline in orders and production disruptions. However, this action was deemed inconsistent with Law No. 6 of 2023 concerning the Stipulation of Government Regulation in Law No. 2 of 2022 concerning Job Creation into Law (Job Creation Law) because it did not meet the elements of proof of efficiency, was not carried out through negotiations with the labor union, and was not accompanied by the provision of normative workers' rights such as severity pay. This study uses a normative legal method with a statute approach. Data was obtained through literature review and interviews with legal experts. The results of the study show that the unilateral termination of employment by PT Yihong Novatex Indonesia is not in line with the principles of non-discrimination and worker protection, and there are indications of union busting practices that violate Article 28E paragraph (3) of the 1945 Constitution and Law No. 21 of 2000 concerning Labor Unions. In conclusion, the unilateral termination of employment by PT Yihong Novatex Indonesia does not reflect justice and legal certainty for workers. The settlement of the case through the Bandung Industrial Relations Court (PHI) is an important step in enforcing fair labor laws and strengthening the protection of workers' rights to organize and their welfare in Indonesia.